Roses & bones : myths, tales, and secrets : a collection of three books - Block, Francesca Lia (HarperTeen, 2011)
Retells the Greek myth in which Psyche searches for her lost love and questions her true self; Echo seeks attention and healing from people in Los Angeles; and classic fairy tales set in modern times with a twist.